DEVELOPMENT OF SYSTEM OF THE MULTIPURPOSE CENTERS OF PROVIDING THE STATE AND MUNICIPAL SERVICES TO THE POPULATION (ON THE EXAMPLE OF PRIMORSKY KRAI) - Eugeniya O Zapoleva (RUDN Journal of Public Administration, 2016)
The article deals with improving the quality of the provision and accessibility of public and municipal services. With the rapid development of telecommunications technology procedures for obtaining services and information to signiﬁ cantly expand and modernize the system of provision of public services to the population and reduce the time spent on their production. Today, multi-function centers (MFC) are beginning to take root everywhere for this purpose, allowing in a short time with the help of one window system to obtain the necessary state and municipal services. The article is an example of monitoring satisfaction scores a population of existing forms of cooperation with government agencies, such as the MFC in the Primorsky krai. The study evaluated the performance of services such as schedule the MFC; territorial availability of the MFC; size, equipment, interior space MFC; queuing; the level of service on the part of specialists and others. Monitoring in general showed a high degree of satisfaction of users of public and municipal services on the principle of one window. Although, despite that the participants of the survey is still a number of comments to the work of the multipurpose centers, which are currently in need of elimination.